Access to justice for vulnerable sectors and the use of the Brasilia Rules (and similar elements) as a central aspect of the work of a Constitutional Court - Espinosa-Saldaña Barrera, Eloy (2020)
This article is based on the premise that the constitutional judge cannot and should not forget the limits that are deduced from their condition of authority, and that they have the institutional duty to comply with and enforce the Law, as well as the obligation to enforce rights in general and access to justice in particular. In this sense, the Brasilia Rules are perfectly compatible with the protection of fundamental rights, both in the ordinary and constitutional judiciary.